Strong law of large numbers for ρ*-mixing sequences with different distributions - Guang-Hui Cai (Discrete Dynamics in Nature and Society)
Strong law of large numbers and complete convergence for ρ*-mixing sequences with different distributions are investigated. The results obtained improve the relevant results by Utev and Peligrad (2003).